IMF Staff papers : Volume 41 No. 4. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1994)
The paper presents a model of optimum currency areas using a general equilibrium approach with regionally differentiated goods. The choice of a currency union depends upon the size of the underlying disturbances, the correlation between these disturbances, the costs of transactions across currencies, factor mobility across regions, and the interrelationships between demand for different goods. It is found that, while a currency union can raise the welfare of the regions within the union, it unambiguously lowers welfare for those outside the union. [JEL F33, F36].
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet